2012
DOI: 10.1111/j.1442-200x.2011.03551.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cerebrospinal fluid in newborns and in infants ≤2 months old with or without meningitis

Abstract: In the case of meningitis with negative CSF culture and Gram stain, diagnosis can be made on CSF parameters, clinical and laboratory findings and suspicion of meningitis. Therefore, a clinical prediction rule to classify risk for bacterial meningitis on evaluation of CSF parameters in any region should be established. More regional trials are needed to enhance the probability of diagnosis according to CSF parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Early recognition of meningitis infants at risk of poor prognosis would be helpful in providing prompt management and identifying those who warrant long-term follow-up and early intervention [ 23 25 ]. Previous studies showed a number of possible early markers of poor prognosis in neonatal meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition of meningitis infants at risk of poor prognosis would be helpful in providing prompt management and identifying those who warrant long-term follow-up and early intervention [ 23 25 ]. Previous studies showed a number of possible early markers of poor prognosis in neonatal meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved 371 studies with 427 study periods performed from January 1, 1935, to December 31, 2019, in 108 countries, describing 157 656 episodes of community-acquired bacterial meningitis. 5, Of the 33 295 episodes for which the patients' sex was reported, 13 452 (40%) occurred in females ( 25,29,32,38,42,43,45,49,55,63,70,86,93,97,101,105,121,126,127,132,133,138,142,157,159,160,196,200,212,214,216,220,235,241,258,275,281,294,297,299,307,319,321,323,324,336,340,345,346,358,365,…”
Section: Resultsmentioning
confidence: 99%
“…The design was observational in 330 studies (94%) and interventional in 20 (6%) studies, with 12 to 22 831 (median [IQR], 115 [61-270]) episodes per study, and the inclusion period’s length varying from 3 months to 36 years (median [IQR], 5 [2-10] years). Studies included neonates (59 studies [16%]; 6549 episodes [4%]), children (101 studies [27%]; 21 511 episodes [14%]), adults (64 studies [17%]; 15 362 episodes [10%]), neonates and children (68 studies [18%]; 26 992 episodes [17%]),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation